2019
DOI: 10.25177/jfst.4.4.ra.530
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant activities of piperine on t-BHP-induced in Ac2F cells

Abstract: Background: In this study, to investigate whether piperine, an alkaloid from Pipper longum, could potentially exerts its effect for the suppression of inflammation and oxidative stress, we examined the modulatory effects of piperine in tert-butylhydroperoxide (t-BHP)-induced Ac2F rat liver cells. Methods: Anti-inflammatory mechanism of piperine in Ac2F cells were examined by performing western blotting. Results: The piperine exhibited remarkable reduction of intracellular reactive species (RS) levels in t-BHPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Additionally, piperine treatment also reduced the nuclear translocation of p65, p50, c-Rel subunits of NF-kappaB and other transcription factors such as ATF-2, c-Fos and CREB. Piperine inhibits the activation of NF-κB as it suppresses the degradation of IκBα and the translocation of p65 from the cytosol to the nucleus ( Pradeep and Kuttan, 2004 ; Chung, 2019 ; Yang et al, 2019 ). Additionally, recent docking studies revealed that piperine exhibits significant binding affinity toward the spike glycoprotein of SARS-CoV-2 and the ACE2 receptor.…”
Section: Natural Immunosuppressant Agents- Adjuvants To Target the Cymentioning
confidence: 99%
“…Additionally, piperine treatment also reduced the nuclear translocation of p65, p50, c-Rel subunits of NF-kappaB and other transcription factors such as ATF-2, c-Fos and CREB. Piperine inhibits the activation of NF-κB as it suppresses the degradation of IκBα and the translocation of p65 from the cytosol to the nucleus ( Pradeep and Kuttan, 2004 ; Chung, 2019 ; Yang et al, 2019 ). Additionally, recent docking studies revealed that piperine exhibits significant binding affinity toward the spike glycoprotein of SARS-CoV-2 and the ACE2 receptor.…”
Section: Natural Immunosuppressant Agents- Adjuvants To Target the Cymentioning
confidence: 99%
“…Piperine treatment also reduced nuclear translocation of NF-kB subunits p65, p50, and c-Rel, as well as another transcription factors like c-Fos, CREB, and ATF-2. Piperine inhibits NF-κB activation by slowing down IκBα breakdown and p65 translocation from the cytoplasm towards the nucleus (Chung, 2019). Piperine also has a strong binding affinity for the SARS-CoV-2 spike glycoprotein and the ACE2 receptor.…”
Section: -Methoxy-4-prop-2-enylphenolmentioning
confidence: 99%